Efficacy and safety of oxantel pamoate in school-aged children infected with Trichuris trichiura on Pemba Island, Tanzania: a parallel, randomised, controlled, dose-ranging study. Issue 1 (January 2016) - Moser, Wendelin; Ali, Said M; Ame, Shaali M; Speich, Benjamin; Puchkov, Maxim; Huwyler, Jörg; Albonico, Marco; Hattendorf, Jan; Keiser, Jennifer
Summary: Background: Commonly used drugs for preventive chemotherapy against soil-transmitted helminths (ie, albendazole and mebendazole) show low efficacy against Trichuris trichiura . Recent studies with oxantel pamoate revealed good cure rates and high egg-reduction rates against T trichiura . We aimed to assess the nature of the dose–response relation to determine the optimum dose. Methods: We did a parallel, randomised, placebo-controlled, single-blind trial with oxantel pamoate in school-aged children (aged 6–14 years) infected with T trichiura on Pemba Island, Tanzania. Children were asked to provide two stool samples and children positive for T trichiura were eligible to participate in the trial. Children were excluded if they suffered from any systematic illness. Children were randomly assigned to six different oxantel pamoate doses (5–30 mg/kg) or a placebo. Randomisation was stratified by baseline infection intensity using random block sizes of seven and 14. The primary endpoints were cure rates and egg-reduction rates against T trichiura, both analysed by available case. Drug safety was assessed 2 h and 24 h after treatment. The trial is registered atwww.isrctn.com, number ISRCTN86603231. Findings: Between Oct 14, and Nov 28, 2014, we enrolled 480 participants and randomly assigned 350 children to the different oxantel pamoate doses or the placebo. 5 mg/kg oxantel pamoate was the minimum effective dose (10 of 46 children cured [cure rate 22%, 95% CI 11–36]; egg-reduction rate 85·0%, 64·5–92·9). An increased probability of being cured and reduced egg counts with escalating doses was recorded. At 25 mg/kg oxantel pamoate 27 of 45 children were cured (cure rate 60%, 95% CI 44–65) with an egg-reduction rate of 97·5% (94·4–98·9), and at 30 mg/kg 27 of 46 children were cured (59%, 43–73) with an egg-reduction rate of 98·8% (96·8–99·6). Oxantel pamoate was well tolerated across all treatment groups; only mild adverse events were reported by the participants 2 h (27 [10%]) and 24 h (12 [4%]) after treatment. Interpretation: Our dose-finding study revealed an excellent tolerability profile of oxantel pamoate in children infected with T trichiura . An optimum therapeutic dose range of 15–30 mg/kg oxantel pamoate was defined. With a weight independent dose of 500 mg oxantel pamoate 95% of children aged 7–14 years in sub-Saharan Africa would receive doses of 11·7–32·0 mg/kg. Future research should include studies with oxantel pamoate in younger children and on different continents with the ultimate goal to be able to add oxantel pamoate to soil-transmitted helminth control programmes. Funding: Swiss National Science Foundation.